The Influence of Nucleating Agents and Process Parameters on Phase Structure of Isotactic Polypropylene and its Copolymer with 3% Ethylene - Jakubicek, Josef; Hribova, Martina; Kucera, Jaroslav; Kubisova, Milena (Manufacturing Technology Journal, 2016)
The homopolymer of the isotactic polypropylene (iPP) and the random copolymer of the isotactic polypropylene and 3% ethylene (iPPE) were used in this study. Isotactic polypropylene can be prepared in α, β and γ morphological phases depending on its crystallization conditions. The phase β content has a strong influence on mechanical, optical and thermal properties. The samples with nucleating agents (NA) α and β were used. Various process parameters were used to prepare melted samples: two thicknesses and three different cooling regimes. Wide-angle X-ray scattering (WAXD) and scanning electron microscopy (SEM) were used to investigate the phase structure. The results show that iPP without nucleation agents (4mm,
Keywords: nucleation; isotactic polypropylene; crystallization